2002
DOI: 10.1046/j.1365-2141.2002.03381.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the recombinant soluble human tumour necrosis factor receptor (p75)‐Fc fusion protein in patients with myelodysplastic syndrome

Abstract: Summary. Laboratory observations suggest that, in some myelodysplastic syndromes (MDS), immune mechanisms may contribute to the impaired blood cell production. Tumor necrosis factor α (TNF‐α), a potent inhibitor of haematopoiesis, has been hypothesized to mediate suppressive effects in MDS: TNF‐α levels are elevated and correlated with marrow apoptosis and cytopenia. Inhibition of TNF‐α production using the soluble TNF receptor (Enbrel) has been successful in rheumatoid arthritis, and we have now applied the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…In fact, anti-TNF therapeutic strategies (monoclonal antibodies and TNF receptor blockers) have only shown minimal clinical efficacy. [9][10][11] Thus it would be important to identify common signaling pathways that would be regulated by many cytokines. Our previous studies have established that Interferons (IFNab and g), TGFb and TNFa can activate members of the MAP (mitogen activated protein kinases) family of kinases, including Erk-kinase and the p38 Map kinase.…”
Section: P38 Mapk Regulates Cytokine Induced Inhibition Of Normal Hemmentioning
confidence: 99%
“…In fact, anti-TNF therapeutic strategies (monoclonal antibodies and TNF receptor blockers) have only shown minimal clinical efficacy. [9][10][11] Thus it would be important to identify common signaling pathways that would be regulated by many cytokines. Our previous studies have established that Interferons (IFNab and g), TGFb and TNFa can activate members of the MAP (mitogen activated protein kinases) family of kinases, including Erk-kinase and the p38 Map kinase.…”
Section: P38 Mapk Regulates Cytokine Induced Inhibition Of Normal Hemmentioning
confidence: 99%
“…sTNFRs compete with membrane-bound receptors for available TNF-␣, but cannot induce cell signaling, and thus function as specific inhibitors of TNF activity in target tissues (26,27). sTNFRI and sTNFRII have both been effectively used to block TNF-␣-mediated immunostimulation in the treatment of immunological disorders such as rheumatoid arthritis and experimental autoimmune encephalomyelitis (28,29). However, it remains unclear whether blockade of TNF-␣ by sTNFRI can inhibit the maturation of DC and potentiate imDC tolerogenicity.…”
mentioning
confidence: 99%
“…87 At NIH, only 1 patient of 15 evaluable became temporarily red cell transfusion-independent (as did a patient in an Italian case report); 89 progression to leukemia was seen in 3 cases. 88 In both trials, TNF had inconsistent effects on marrow hematopoietic progenitor cell growth pre-and post-treatment, nor was there correlation with TNF plasma levels.…”
Section: Soluble Tnf Receptormentioning
confidence: 99%
“…In small pilot trials from multiple institutions, the soluble receptor, Enbrel, has been well tolerated, but treatment has produced very modest clinical responses in a minority of patients. [87][88][89] In one study from Seattle and Stanford, among 12 evaluable patients, 4 showed increased hemoglobin levels, and 2 each also had somewhat higher platelet or neutrophil numbers. 87 At NIH, only 1 patient of 15 evaluable became temporarily red cell transfusion-independent (as did a patient in an Italian case report); 89 progression to leukemia was seen in 3 cases.…”
Section: Soluble Tnf Receptormentioning
confidence: 99%